A scoping review of prehabilitation interventions for arthroplasty patients - Prithi Pillay-Jayaraman; Verusia Chetty; Stacy Maddocks (AOSIS, 2023)
Background: Osteoarthritis (OA) is a long-term condition that causes significant impairment, and because of the increasing prevalence of OA, the demand for arthroplasty will continue to rise. However, the demand will not be matched by availability, because of prioritisation of trauma-related surgeries. Implementing prehabilitation could assist physiotherapists in having an impact on improving access by reducing the length of stay. Objectives: The aim of our scoping review was to explore, map and identify trends and gaps to better inform the content of a prehabilitation programme. Method: In our scoping review, studies between 1995 and 2020 were identified and included based on inclusion and exclusion criteria and study methodology described by Arksey and O'Malley. The results were collated and summarised as a narrative synthesis. Results: A total of 200 articles were identified and exported from four databases of which 48 articles were included in the final analysis. Regarding the efficacy of prehabilitation interventions, 21 studies reported significant results supporting prehabilitation, whereas 11 studies reported non-significant results. Conclusions: Prehabilitation could be a valuable adjunct in reducing length of hospital stay and improving functional outcomes in adults undergoing total joint replacement. Clinical implications: The scoping review described the information available on prehabilitation in lower limb arthroplasty patients and could potentially inform the design of a prehabilitation programme suitable for use in the South African public health context.